From despair to hope HOPE VI and the new promise of public housing in America's cities - Cisneros, Henry; Engdahl, Lora (Brookings Institution Press, 2009)
"Documents the evolution of HOPE VI, exploring what it accomplished replacing severely distressed public housing with mixed-income communities and where it fell short. Reveals how a program conceived to address a specific problem triggered a revolution in public housing and solidified principles that still guide urban policy today"--Provided by publisher.